A sufficient and necessary condition of existence of blow-up radial solutions for a k-Hessian equation with a nonlinear operator - Zhang, Xinguang; Liu, Lishan; Wu, Yonghong; Cui, Yujun (Nonlinear Analysis: Modelling and Control, 2020)
In this paper, we establish the results of nonexistence and existence of blow-up radial solutions for a k-Hessian equation with a nonlinear operator. Under some suitable growth conditions for nonlinearity, the result of nonexistence of blow-up solutions is established, a sufficient and necessary condition on existence of blow-up solutions is given, and some further results are obtained.